(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس هذا البحث القطاع المصرفي السوري وأهم التطورات التي حدثت فيه نتيجة دخول المصارف الخاصة إلى السوق السورية ويتعرض إلى المشكلة الأهم التي تعاني منها هذه المصارف وهي تراكم السيولة الغير موظفة فيها وتوظيف نسبة كبيرة من أموالها الموظفة في مجالات غير منتجة وذلك نتيجة لعدة أسباب أهمها غياب سوق الأوراق المالية في سورية خلال السنوات السابقة, وقد تمت دراسة ومقارنة السياسة الاستثمارية لمصارف عاملة في سورية مع مصارف عاملة في دول عربية موجود فيها سوق للأوراق المالية وذلك بهدف توضيح أهمية هذه السوق لفتح مجال أمام هذه المصارف لتوظيف أموالها بما يحقق لها العوائد التي ترجوها. This research studies the banking sector in Syria and its most important developments that had occurred as a result of private banks existence in the Syrian market. And it focuses on the most important problems facing these banks, which are: the accumulation of non-employed liquidity and the employment of a large proportion of its funds in non-productive fields, this due to a variety of reasons the most important of them is the absence of market securities in Syria during the previous years. Also this research studies and compares the investment policy of several banks in Syria with several banks in Arab states which contain a stock market, in order to reveal the importance of a stock market in making opportunities for these banks to invest their money in order to achieve its targeted revenues.